Good Corporate Governance Dalam Konteks Syariah Islam: Studi Kasus Bank Syariah Indonesia - Putri, Anggi Safrina; chorella, Manisha laisya; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Observations made in this study have the aim of knowing good corporate governance (GCG) information at Indonesian Sharia Banks (BSI). Bank Syariah Indonesia is one of the sharia-based bank companies in Indonesia. BSI is committed to improving and increasing consistency in the implementation of GCG principles in all business aspects. In Islamic sharia we are also taught about responsibility, transparency, accountability, responsibility, independence and fairness that has been determined. The research method used is an analysis with a qualitative approach which is examined in research on how to apply the principles of Good Corporate Governance in Indonesian Sharia Banks. In its application, Good Corporate (GCG) can run in harmony with the sharia economic system. In addition, the implementation of GCG is expected to be able to improve the performance of Indonesian Sharia Banks.